2006
DOI: 10.1111/j.1365-3040.2006.01610.x
|View full text |Cite
|
Sign up to set email alerts
|

Physiological girdling of pine trees via phloem chilling: proof of concept

Abstract: Quantifying below-ground carbon (C) allocation is particularly difficult as methods usually disturb the rootmycorrhizal-soil continuum. We reduced C allocation below ground of loblolly pine trees by: (1) physically girdling trees and (2) physiologically girdling pine trees by chilling the phloem. Chilling reduced cambium temperatures by approximately 18°C. Both methods rapidly reduced soil CO2 efflux, and after approximately 10 days decreased net photosynthesis (Pn), the latter indicating feedback inhibition. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
2
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 29 publications
6
52
2
1
Order By: Relevance
“…2A,B) suggest such a feedback inhibition. Several girdling studies (Iglesias et al, 2002;Bondada and Syvertsen, 2005;Johnsen et al, 2007;Cheng et al, 2008;Rivas et al, 2008) have reported this P n inhibition which they attributed to the decreased sink demand in girdled trees. In literature two processes are described which might trigger inhibition of P n : stomatal closure (Williams et al, 2000;Cheng et al, 2008;Domec and Pruyn, 2008) and damage to the photosynthesis system (Myers et al, 1999;Bondada and Syvertsen, 2005;Rivas et al, 2008).…”
Section: Discussion Double Girdling Affects Both the Carbon And Watermentioning
confidence: 95%
See 1 more Smart Citation
“…2A,B) suggest such a feedback inhibition. Several girdling studies (Iglesias et al, 2002;Bondada and Syvertsen, 2005;Johnsen et al, 2007;Cheng et al, 2008;Rivas et al, 2008) have reported this P n inhibition which they attributed to the decreased sink demand in girdled trees. In literature two processes are described which might trigger inhibition of P n : stomatal closure (Williams et al, 2000;Cheng et al, 2008;Domec and Pruyn, 2008) and damage to the photosynthesis system (Myers et al, 1999;Bondada and Syvertsen, 2005;Rivas et al, 2008).…”
Section: Discussion Double Girdling Affects Both the Carbon And Watermentioning
confidence: 95%
“…Double girdling completely blocks the downward phloem transport from the leaves to the roots, while the upward water flow from the roots to the leaves is maintained (Daudet et al, 2005;Johnsen et al, 2007). Accordingly, the carbon status of the trees was changed, since the roots could no longer function as a major sink for new assimilates after double girdling.…”
Section: Discussion Double Girdling Affects Both the Carbon And Watermentioning
confidence: 99%
“…Nevertheless, the model fitted better with 2014 growth rates. Johnsen et al (2007) mentioned that girdling is destructive and irreversible. Ultimately, our study showed that the Scots pine trees managed to survive for two years.…”
Section: Discussionmentioning
confidence: 99%
“…Thermocouples were inserted into pin-sized openings in the bark created with a stylus to the depth of the cambium to continuously monitor phloem temperature of each branch. Cooling of phloem tissues was achieved by circulating chilled liquid (ethylene glycol) from a cold-block system through plastic tubing encircling branches, similar to the system used by Johnsen et al (2007). Branches assigned to the cooling treatment were wrapped with flexible plastic tubing to create a 30 cm long collar that was then covered with insulation.…”
Section: Branch Cooling and Collection Of Plant Materialsmentioning
confidence: 99%